2022
DOI: 10.1136/bmjopen-2021-051881
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of polypharmacy in community-dwelling older adults from seven centres in five European countries: a cross-sectional study of DO-HEALTH

Abstract: ObjectiveTo investigate the prevalence of polypharmacy and characteristics associated with polypharmacy in older adults from seven European cities.DesignCross-sectional study of baseline data from DO-HEALTH.Setting and participantsDO-HEALTH enrolled 2157 community-dwelling adults age 70 and older from seven centres in Europe. Participants were excluded if they had major health problems or Mini-Mental State Examination Score <24 at baseline.Primary outcome measuresExtensive information on prescription and ov… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…Compared with other populations, the public service population was particularly specific because several socio-demographic variables, usually known to impact KAP demonstrated no significant effect in our study. Sex, education level, marital status and the fact of suffering from a chronic disease that have been identified as determinants in other studies [ 32 , 33 , 34 , 35 ] did not statistically modify the KAP in this public service population. However, the occupational status, which is mainly linked to age but not only, allowed for the dichotomization of the sample respondents between workers and retired.…”
Section: Discussionmentioning
confidence: 43%
“…Compared with other populations, the public service population was particularly specific because several socio-demographic variables, usually known to impact KAP demonstrated no significant effect in our study. Sex, education level, marital status and the fact of suffering from a chronic disease that have been identified as determinants in other studies [ 32 , 33 , 34 , 35 ] did not statistically modify the KAP in this public service population. However, the occupational status, which is mainly linked to age but not only, allowed for the dichotomization of the sample respondents between workers and retired.…”
Section: Discussionmentioning
confidence: 43%
“…30 Furthermore, a large multicentre study, conducted in primary healthcare centres across Europe, reported a polypharmacy prevalence of 27.2% (a range of 16.4% to 60.8%). 31 The variability in the reported prevalence rates of polypharmacy among elderly patients is multifactorial. One reason is the heterogeneity in the definition of polypharmacy among the studies.…”
Section: Discussionmentioning
confidence: 99%
“…A comparison between the perception of patients from the different countries participating in the study shows that patients from Spain and Sweden consider that they have worse attentional or learning capacity, but better functioning of executive functions than patients from Greece and Belgium. While the results obtained pertain to a small sample of patients and may not be entirely representative, we can infer, based on previous literature, that potential differences could be associated with the age of the participants enrolled in the study (despite the Spanish are the older and the Swedish the younger ones), cultural and socioeconomic aspects, the healthcare system and the existing coverage in each country, as well as the available mental health specialists' assistance (De Godoi Rezende Costa Molino et al., 2022).…”
Section: Discussionmentioning
confidence: 99%